Identifying Research Strategies for the Future: Alternatives to the Traditional Doctoral Dissertation - Kathryn A. Sanders (Adult Education Research Conference, 1998)
This study was designed to explore the attitudes and opinions of experts in the fields of adult education and vocational education toward future doctoral research needs and toward potential alternatives to the traditional doctoral dissertation. A three round Delphi and semi-structured interviews were used to gather data.